2018
DOI: 10.1007/s10334-018-0724-6
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine polymer probes for magnetic resonance imaging: quo vadis?

Abstract: Over the last few years, the development and relevance of 19 F magnetic resonance imaging (MRI) for use in clinical practice has emerged. MRI using fluorinated probes enables the achievement of a specific signal with high contrast in MRI images. However, to ensure sufficient sensitivity of 19 F MRI, fluorine probes with a high content of chemically equivalent fluorine atoms are required. The majority of 19 F MRI agents are perfluorocarbon emu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
142
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(151 citation statements)
references
References 105 publications
1
142
0
3
Order By: Relevance
“…Magnetic resonance imaging (MRI) is a well-established non-invasive diagnostic method. The most widely used proton 1 H MRI has found a vast range of applications clinically and in research, but certain anatomical and/or pathological structures are hard or impossible to visualise [ 1 , 2 , 3 ]. To overcome this problem, a T 1 (or less commonly T 2 ) contrast agent (CA) can be employed as they accumulate in certain tissues and alter their relaxation properties, thus enabling their visualisation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Magnetic resonance imaging (MRI) is a well-established non-invasive diagnostic method. The most widely used proton 1 H MRI has found a vast range of applications clinically and in research, but certain anatomical and/or pathological structures are hard or impossible to visualise [ 1 , 2 , 3 ]. To overcome this problem, a T 1 (or less commonly T 2 ) contrast agent (CA) can be employed as they accumulate in certain tissues and alter their relaxation properties, thus enabling their visualisation.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, 19 F MRI small-molecule tracers suffer from strong fluorophilicity, leading to excessive hydrophobicity, which often causes an unfavourable biodistribution in the human body. This problem can be overcome by using macromolecular fluorinated tracers, whose biodistribution can be tailored to the required application by varying the polymer composition and architecture [ 3 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To eliminate this issue, increasing the amount of magnetically equivalent fluorine atoms per molecule is needed. This can be done either through attaching additional CF3 groups to the probe or through conjugating the probe to perfluorinated macromolecules, which are currently used to track the cell activity in vivo using MRI [ 110 , 111 ]. A higher affinity of fluorescence probes allows the reduction of the background signal due to nonspecific binding and, therefore, tends to increase the signal-to noise-ratio (SNR).…”
Section: Discussionmentioning
confidence: 99%
“…However, ionic gadolinium complexes can leak toxic Gd 3+ ions with short half-life and it has been reported that Gd 3+ chelates can lead to renal insufficiency (Rashid et al, 2016;Marasini et al, 2020). Fluorinated small molecules that bind to amyloid plaques can be detected by 19 F MRI (Jirak et al, 2019). But for their low in vivo concentrations, this method might be difficult to be applied to human clinical medicine (Sillerud et al, 2013).…”
Section: Commonly Used Mri Casmentioning
confidence: 99%